A Proposal for Certification in Nursing Theory - Debra R. Hanna (Universidad de La Sabana, 2016)
The author proposes the development of different levels of certification in the knowledge of nursing theory that would be based on the level of formal education attained. At present, nurses are being required to obtain higher levels of formal education in order to serve patients safely in a technologically complex health care system. Although evidence-based practice is strongly desired in contemporary health care, less consideration has been given to the value of theory-based nursing practice or the relationship between theory and research. The author explains multiple background issues and then highlights several questions that are important for disciplinary discussion at this point in time. Doi: 10.5294/aqui.2016.16.1.2